Omecamtiv mecarbil and Mavacamten target the same myosin pocket despite opposite effects in heart contraction - Daniel Auguin; Julien Robert-Paganin; Stéphane Réty; Carlos Kikuti; Amandine David; Gabriele Theumer; Arndt W. Schmidt; Hans-Joachim Knölker; Anne Houdusse (Nature Communications, 2024)
Abstract Inherited cardiomyopathies are common cardiac diseases worldwide, leading in the late stage to heart failure and death. The most promising treatments against these diseases are small molecules directly modulating the force produced by β-cardiac myosin, the molecular motor driving heart contraction. Omecamtiv mecarbil and Mavacamten are two such molecules that completed phase 3 clinical trials, and the inhibitor Mavacamten is now approved by the FDA. In contrast to Mavacamten, Omecamtiv mecarbil acts as an activator of cardiac contractility. Here, we reveal by X-ray crystallography that both drugs target the same pocket and stabilize a pre-stroke structural state, with only few local differences. All-atom molecular dynamics simulations reveal how these molecules produce distinct effects in motor allostery thus impacting force production in opposite way. Altogether, our results provide the framework for rational drug development for the purpose of personalized medicine.